SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2118/110368-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Numerical Simulations and Laboratory Waterfloods in Fractured Carbonates

Abstract: Recovery mechanisms in fractured carbonate rocks have been investigated by comparing laboratory experiments with numerical simulations. The experimental data include waterfloods in blocks of carbonate rock with 2D, in-situ fluid saturation of the advancing waterfronts. The waterfloods were initially performed on the whole block, and then repeated on the same block with a fracture network containing both closed and open fractures to isolate the effect from fractures. The primary objective for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Several studies have shown that recovery by spontaneous imbibition (SI) is improved when wettability turns toward waterwet (Anderson 1987;Zhou et al 2000;Strand et al 2006). The combined effect of fracture flow and wettability was demonstrated in the work of Graue et al (2001) and Haugen et al (2007Haugen et al ( , 2008Haugen et al ( , 2010. Blocks of porous media with defined fracture surfaces were flooded with water, and the impact of wettability was demonstrated by imbibition of water into the water-wet blocks and negligible imbibition into the oil-wet blocks as observed with magnetic-resonance-imaging techniques.…”
Section: Previous Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that recovery by spontaneous imbibition (SI) is improved when wettability turns toward waterwet (Anderson 1987;Zhou et al 2000;Strand et al 2006). The combined effect of fracture flow and wettability was demonstrated in the work of Graue et al (2001) and Haugen et al (2007Haugen et al ( , 2008Haugen et al ( , 2010. Blocks of porous media with defined fracture surfaces were flooded with water, and the impact of wettability was demonstrated by imbibition of water into the water-wet blocks and negligible imbibition into the oil-wet blocks as observed with magnetic-resonance-imaging techniques.…”
Section: Previous Experimental Workmentioning
confidence: 99%
“…They also illustrated that fracture relative permeabilities can become highly nonlinear because of the interplay of gravity, surface roughness, and aperture. Haugen et al (2007) compared in-situ oil displacement obtained by magnetic resonance imaging with numerical simulations, and noted that some features could only be matched with a varying-fracture capillary pressure.…”
Section: System Description and Modelingmentioning
confidence: 99%